PENGEMBANGAN MEDIA PEMBELAJARAN AR BERBANTUAN ASSEMBLR EDU TYPE MERGE CUBE DALAM MATERI IPAS KELAS V - Maysaroh, Luluk; Purnawanto, Ahmad Teguh; Mariyani, Anna (Program Studi Pendididikan Guru Sekolah Dasar Fakultas Keguruan dan Ilmu Pendidikan Universitas Riau, 2025)
This research is motivated by the minimal use of interesting and enjoyable learning media, as well as the absence of learning media.ARat SDN 1 Gempolrejo. Learning media is still in printed form, so the display is less attractive and the variations are limited, so students feel bored. This study aims to develop Augmented Reality (AR)-based learning media using the Assemblr Edu platform in the form of a Merge Cube, and to test the feasibility of the resulting product. The media developed is a 3D visual material that can be accessed via QR Code on the sides of the Merge Cube. The method used is Research and Development (R&D) with the ADDIE model (Analisys, Design, Development, Implementation, Evaluation). The subjects of the study were 24 fifth-grade students of SDN 1 Gempolrejo. Data collection techniques included interviews, questionnaires, and documentation; data were analyzed qualitatively and quantitatively from 3 media validators, namely design experts, material experts, and language experts as well as the results of small group student trials, large group trials, and from fifth-grade teachers. The validation results showed that the media was very suitable for use, with an assessment from design experts of 97%, material experts 80%, and language experts 94%. Student responses showed high interest (91%) and teachers rated the media as very interesting (94%). Thus, this media was declared valid, interesting, and suitable for use as a reference for science learning, especially natural disaster material.